Avaliação da função pulmonar e da força muscular respiratória de crianças com asma e/ou rinite submetidas ao teste de caminhada de seis minutos - Soares, Ana Alice de Almeida (2016)
Introduction: Rhinitis and asthma have high rates of prevalence and morbidity and are responsible for reduced quality of life of patients, compromising their daily activities. The coexistence of both diseases in the same individual is well documented, aside from rhinitis acting as a risk factor for the future emergence of asthma. Studies show worsening of lung function in children with asthma after physical exercise on a treadmill, but those using submaximal tests for the assessment of children are rare, especially with mild asthma. The 6-minute walk test (6MWT) is a tool of great applicability in pediatrics, that reflects the performance in daily life activities and assesses the level of physical ability of children with effort limitation. Objectives: To evaluate respiratory muscle strength (MIP and MEP) and lung function (flows and volumes) of children with rhinitis and/or asthma before and after the 6MWT, and compare them with the performance of healthy children. Methods: This is a cross-sectional analytical study with children 6-12 years old, in outpatient follow-up. Results: 115 children were included, being 27 healthy (H), 31 with rhinitis (R) and 57 with asthma (A), which was classified as mild (31 with controlled asthma and 26 with partial control). Of the total population, 66 children (57.4%) reported regular physical activity. From group A, 94.73% had associated rhinitis. There were no significant differences in anthropometric measurements, demographics data and level of physical activity between the groups. The total distance covered in 6MWT and measured vital signs before and after the test were similar among the three groups. However, children with asthma had worst performance, covering a distance lower than expected for their age, weight and height (p = 0.0007), regardless of disease control. MIP, FEV1, FEF 25-75 and FEV1/FVC were lower in group A related to the R and H groups before and after the 6MWT. Compared to the pre-test values, MIP increased, in addition to FEV1/FVC and FEF 25-75 which fell significantly after the 6MWT, only in groups A and R. Conclusion: Asthmatic children showed lower values of respiratory muscle strength and lung function when compared to children with rhinitis and healthy. Children with rhinitis, with no clinical history of asthma, behaved similarly to the asthmatic, as regards the respiratory muscle strength and evolution of pulmonary function after 6MWT, increasing the concept of united airways. Submaximal exercises can compromise respiratory muscle strength and lung function of children with rhinitis and/or asthma.